2017
DOI: 10.1039/c7ew00134g
|View full text |Cite
|
Sign up to set email alerts
|

The microbial colonization of activated carbon block point-of-use (PoU) filters with and without chlorinated phenol disinfection by-products

Abstract: Activated carbon based point-of-use drinking water filters change the bacterial community structure and increase the absolute abundance of genera, including those associated with opportunistic pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 65 publications
(73 reference statements)
1
30
0
Order By: Relevance
“…It has been seen, for example, that the application of carbon filters may result in a greater presence of Legionella in water because the bacterium can colonize the filters while passing through [ 99 , 100 ]. On the contrary, membrane filters have shown to control the colonization of hospital water systems up to 2–8 weeks of continuous use [ 101 , 102 ], especially when they are covered with a silver layer [ 103 ].…”
Section: Disinfection Strategiesmentioning
confidence: 99%
“…It has been seen, for example, that the application of carbon filters may result in a greater presence of Legionella in water because the bacterium can colonize the filters while passing through [ 99 , 100 ]. On the contrary, membrane filters have shown to control the colonization of hospital water systems up to 2–8 weeks of continuous use [ 101 , 102 ], especially when they are covered with a silver layer [ 103 ].…”
Section: Disinfection Strategiesmentioning
confidence: 99%
“…For example, multiple studies that rely on culture-based methods have shown that heterotrophic bacterial counts increase with time in the effluent of ACB PoU filters to levels that exceed those in the tap water influent, even when used within the manufacturers' recommended usage period. [7][8][9][10] Other culture-based studies found that the composition of bacteria in the filter effluent was different from the tap water. [10][11][12] Chaidez et al (2004) found that indigenous Aeromonas hydrophila, Pseudomonas aeruginosa and total coliforms were more abundant in the effluent than in the influent using culture-based techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Other culture-based studies found that the composition of bacteria in the filter effluent was different from the tap water. [10][11][12] Chaidez et al (2004) found that indigenous Aeromonas hydrophila, Pseudomonas aeruginosa and total coliforms were more abundant in the effluent than in the influent using culture-based techniques. 11 Using culture-independent techniques, studies have similarly found that ACB PoU filters significantly alter the bacterial abundance and composition in filter effluents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations